Pemberdayaan Ekonomi Perempuan melalui Usaha Mikro: Kasus Pembuatan Triplek di Desa Jerukgiling Kabupaten Kendal - Muhammad Husain As Sajjad; Syifa Fairuzzahra Putri Angrianingtyas; Zeva Ega Sekarrisma; Aida Rahmawati; Hanin Aisya Fakihati; Najichah (Lembaga Pengembangan Kinerja Dosen, 2024)
This study examines microeconomic activities in the form of part-time plywood manufacturing in Jerukgiling Village, Kendal Regency, which has been running for two years and involves ten workers. Plywood production is carried out by housewives as an additional job after completing household chores and activities in the rice fields. With a price of Rp1,200 per sheet, plywood production provides additional income for families in the village. The raw materials for making plywood come from sengon and jagon wood, provided by Mr. Gunawan, a boss from Brayu Hamlet, Kertosari Village, Singorojo Subdistrict, Kendal District. The production process is carried out in a special place that is now available, unlike before when it was done in each house. Plywood is collected every day with a production quantity of 200-300 pieces, although payment is made at a later date. The study also found that working hours are flexible, with production activities extending into the evening. The health center routinely checks the health of the workers every month to ensure that their health conditions are maintained. The analysis concludes that this plywood-making business not only provides economic benefits, but also provides flexibility for housewives in carrying out their dual roles. The main resource person for this research was Mrs. Karomah, one of the workers, who provided a detailed description of the dynamics and challenges faced in running a plywood-making business while taking care of their children